Passing “The Imitation Game”: Ex Machina, the Ethical, and Mimetic Theory - Goodhart, Sandor ca. 20./21. Jh. (Mimetic theory and film, 2019)
René Girard’s theories have become increasingly well-known in the past few years. Desire in human beings, Girard famously argued, is borrowed, appropriated from others rather than originating from demands within us or exigencies external to us. Desire, for Girard, is never desire either for the object or for the subject but rather selon l’autre, according to the other individual in our world (or outside of it) we have identified as our mediator or model. Primitive cultures, communities that ethnologists name as “archaic” and that historically preceded our own, control or manage such appropriated desire through a set of distinctions between the sacred and violence, distinctions that always derive from a system at whose center remains a sacrificial exclusion, a “scapegoat mechanism,” a lynching or collective murder of a surrogate victim, and the genesis in its wake of new social order, new configurations of difference and identity....